Dynamic Interactions Between Brilliant Green and MscL Investigated by Solid‐State NMR Spectroscopy and Molecular Dynamics Simulations. Issue 3 (21st November 2022) - Ma, Shaojie; Zhang, Yan; Zhang, Xuning; Xie, Huayong; Tong, Qiong; Yu, Kunqian; Yang, Jun
Abstract: The mechanosensitive ion channel of large conductance (MscL) is a promising template for the development of new antibiotics due to its high conservation and uniqueness to microbes. Brilliant green (BG), a triarylmethane dye, has been identified as a new antibiotic targeted MscL. However, the detailed binding sites to MscL and the dynamic pathway of BG through the MscL channel remain unknown. Here, the dynamic interactions between BG and MscL were investigated using solid‐state NMR spectroscopy and molecule dynamics (MD) simulations. Residue site‐specific binding sites of BG to the MscL channel were identified by solid‐state NMR. In addition, MD simulations revealed that BG conducts through the MscL channel via residues along the inner surface of the pore sequentially, in which the strong hydrophobic interactions between BG and hydrophobic residues F23 and I27 in the hydrophobic gate region of the MscL channel are major restrictions. Particularly, it was demonstrated that BG activates the MscL channel by reducing the hydrophobicity of the F23 in the gate region by water molecules that are bound to BG. Taken together, these simulations and experimental data provide novel insights into the dynamic interactions between BG and MscL, based on which new hydrophobic antibiotics and adjuvants targeting MscL can be developed. Abstract : Solid‐state NMR and molecular dynamics simulations were performed to study the dynamic pathway of triarylmethane dye Brilliant Green (BG) through the antimicrobial target MscL protein. Key residues (especially F23 and I27) and the specific processes that act on BG through the Ma‐MscL channel are identified, and proof is presented that BG activates the hydrophobic gate of Ma‐MscL by its bound water molecules.